2003
DOI: 10.1097/01.asn.0000068462.38661.89
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Weight Loss on Renal Function in Patients with Severe Obesity

Abstract: Abstract. Severe obesity is associated with increased renal plasma flow (RPF) and glomerular filtration rate (GFR). The aim of the present study was to examine whether weight loss may reverse glomerular dysfunction in obese subjects without overt renal disease. Renal glomerular function was studied in eight subjects with severe obesity (body mass index [BMI] 48.0 Ϯ 2.4) before and after weight loss. Nine healthy subjects served as controls. GFR and RPF were determined by measuring inulin and PAH clearance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
341
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(374 citation statements)
references
References 43 publications
18
341
3
6
Order By: Relevance
“…48 The decrease in GFR and arterial pressure after WL is comparable with this hypothesis. Chagnac et al, 15 however, reported that obesity-related glomerular hyperfiltration was improved after WL in morbidly obese subjects as assessed using insulin and p-aminohippuric acid clearance. In the present study, we also observed that several subjects did not improve CCr as calculated using the Cockcroft-Gault equation, even though their creatinine levels decreased with WL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 The decrease in GFR and arterial pressure after WL is comparable with this hypothesis. Chagnac et al, 15 however, reported that obesity-related glomerular hyperfiltration was improved after WL in morbidly obese subjects as assessed using insulin and p-aminohippuric acid clearance. In the present study, we also observed that several subjects did not improve CCr as calculated using the Cockcroft-Gault equation, even though their creatinine levels decreased with WL.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,6 Furthermore, several large cohort studies have demonstrated close associations between obesity, especially abdominal obesity and the onset of chronic kidney disease (CKD) [7][8][9][10][11] and faster CKD progression. 10 Intentional weight loss (WL) reduced the risk of the onset and development of hypertension, 12,13 diabetes 14 and renal injury 15 in overweight or obese individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by the same group, GFR determined by inulin clearance in eight participants with severe obesity decreased from 145±14 to 110±7 ml/min 12 months after gastroplasty, with a concomitant 32% decrease in BMI [36]. However, in both of the above studies, GFR was not corrected for body surface area.…”
Section: Hyperfiltration Independent Of Diabetesmentioning
confidence: 94%
“…Weight loss, either after bariatric surgery or after lifestyle modification, normalizes blood glucose (4) and decreases BP and plasma lipids (5,6) in obese patients. Similarly, a significant reduction in urinary albumin excretion and glomerular hyperfiltration has been reported in morbidly obese patients with a dramatic decrease of body mass index (BMI) (7,8). Moreover, even a small decrease in BMI is related to the reduction of proteinuria in patients with diabetic nephropathy and other chronic kidney diseases (9 -11).…”
mentioning
confidence: 96%